2014
DOI: 10.1111/1471-0528.12739
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obstetric fistula: a population‐based study in rural Pakistan

Abstract: Objective To estimate the prevalence of obstetric fistula, its duration and impact on women's daily life using robust data collection methods in a population-based sample in rural Pakistan.Design A population-based, cross-sectional study.Setting A rural community in Sindh Province, Pakistan.Population Randomly selected women aged 15 years or older.Methods A multistage random sampling strategy was used to recruit the women. Lady Health Workers interviewed women in their own homes using a structured questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 19 publications
2
23
1
Order By: Relevance
“…A 2013 systematic review and meta‐analysis found only ten studies that used clinically confirmed cases to estimate community‐based OF prevalence; four of these were conducted in sub‐Saharan Africa or South Asia . Subsequent to the review, two population‐based cross‐sectional studies from southern Sudan and Pakistan used confirmatory clinical examinations; however, neither of these studies used a control population to assess the validity of the screening questions used to identify cases . At present, there is no widely used, well‐validated fistula screening tool.…”
Section: Introductioncontrasting
confidence: 82%
See 1 more Smart Citation
“…A 2013 systematic review and meta‐analysis found only ten studies that used clinically confirmed cases to estimate community‐based OF prevalence; four of these were conducted in sub‐Saharan Africa or South Asia . Subsequent to the review, two population‐based cross‐sectional studies from southern Sudan and Pakistan used confirmatory clinical examinations; however, neither of these studies used a control population to assess the validity of the screening questions used to identify cases . At present, there is no widely used, well‐validated fistula screening tool.…”
Section: Introductioncontrasting
confidence: 82%
“…The OF prevalence estimates from other population‐based studies with confirmatory clinical examinations from sub‐Saharan Africa and South Asia vary widely, and were significantly higher than those found in our study: 162 per 100 000 women (95% CI 153–264) in Ethiopia ( n = 19 153); 95 per 100 000 women (95% CI 2–526) in Gambia ( n = 1038); 30 per 100 000 women (95% CI 10–100) in Southern Sudan ( n = 8865); 86 per 100 000 (95% CI 2–480) in Maharashtra, India ( n = 1167); 260 per 100 000 (95% CI 7–1439) in Karnataka, India; and 390 per 100 000 women (95% CI 220–570) or 450 per 100 000 parous women (95% CI 250–650) in Pakistan ( n = 5064) . Notably, these studies used different sampling methodologies and none of the studies examined controls (women who did not report symptoms of OF).…”
Section: Discussionmentioning
confidence: 99%
“…In this study of 215 Indian women presenting for obstetric fistula care/repair, key findings were generally similar to studies from Pakistan and Bangladesh, including maternal characteristics such as illiteracy or low level of education, low age of marriage (median 18 years), and residing in rural areas or urban slums. In our study, the median age at development of fistula was 26 years, with a median parity of 2.0.…”
Section: Discussionsupporting
confidence: 73%
“…In Malawi, the prevalence of OF is estimated to be 1.6 per 1000 women (1, 2), one of the highest estimates in the world. Previous descriptive studies in sub-Saharan Africa have found that a majority of fistula patients are young, primiparous women with short stature – all factors that contribute to an immature and contracted pelvis, cephalopelvic disproportion, and obstructed labor (3, 4). However, older and multiparous women also develop OF, even though they are less likely to have risk factors for obstructed labor.…”
Section: Introductionmentioning
confidence: 99%